2017
DOI: 10.1183/13993003.02108-2016
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosaadaptation and diversification in the non-cystic fibrosis bronchiectasis lung

Abstract: To characterise Pseudomonas aeruginosa populations during chronic lung infections of non-cystic fibrosis bronchiectasis patients, we used whole-genome sequencing to 1) assess the diversity of P. aeruginosa and the prevalence of multilineage infections; 2) seek evidence for cross-infection or common source acquisition; and 3) characterise P. aeruginosa adaptations.189 isolates, obtained from the sputa of 91 patients attending 16 adult bronchiectasis centres in the UK, were whole-genome sequenced.Bronchiectasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 40 publications
5
61
0
Order By: Relevance
“…Predictors of therapy showed ICS use was, not surprisingly, associated with asthma, but the most striking finding is that patients with chronic Pseudomonas aeruginosa infection had higher rates of use of ICS, macrolides, and inhaled antibiotics, suggesting that US physicians recognize the poor prognosis associated with P aeruginosa and escalate pharmacotherapy accordingly. 8,9 The survey results support the data from the registry in showing that 55% of patients received ICS, whereas 40% received azithromycin, and 15% received inhaled tobramycin. The majority of online survey respondents (77%) had bronchiectasis associated with NTM.…”
supporting
confidence: 69%
“…Predictors of therapy showed ICS use was, not surprisingly, associated with asthma, but the most striking finding is that patients with chronic Pseudomonas aeruginosa infection had higher rates of use of ICS, macrolides, and inhaled antibiotics, suggesting that US physicians recognize the poor prognosis associated with P aeruginosa and escalate pharmacotherapy accordingly. 8,9 The survey results support the data from the registry in showing that 55% of patients received ICS, whereas 40% received azithromycin, and 15% received inhaled tobramycin. The majority of online survey respondents (77%) had bronchiectasis associated with NTM.…”
supporting
confidence: 69%
“…Moreover, the capsule provides protection against desiccation (18). Many highly adaptable Gram-negative rods such as P. aeruginosa can also produce biofilm-associated polysaccharides, becoming part of the most prevalent non-sporulated bacilli in hospital environment (19). As such, though EA inhibited P. aeruginosa growth in low concentrations, it could not efficiently kill it.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we found that CEGs were highly conserved. Niche adaptation through small-scale loss-offunction mutations has been observed in strains including P. aeruginosa and Shigella (52)(53)(54). This result emphasizes that, in order to study auxotrophy development in host-adapted strains, future efforts should expand our workflow for the prediction of bacterial nutrient requirements (which is currently limited to the identification of genetic lesions at the gene level) to account for smaller-scale deleterious mutations.…”
Section: Amino Acid and Vitamin Auxotrophies Confer A Fitness Advantagementioning
confidence: 98%